Urinary bisphenol a concentrations and their implications for human exposure in several Asian countries - Zhang, Z.F.; Alomirah, H.; Cho, H.S.; Li, Y.F.; Liao, C.Y.; Minh, T.B.; Mohd, M.A.; Nakata, H.; Ren, N.Q.; Kannan, K. (2011)
Bisphenol A (BPA) is an industrial chemical used in the manufacture of polycarbonate plastics and epoxy resins. Due to the potential of this compound to disrupt normal endocrinal functions, concerns over human exposure to BPA have been raised. Although several studies have reported human exposure to BPA in Western nations, little is known about exposure in Asian countries. In this study, we determined total urinary BPA concentrations (free plus conjugated) in 296 urine samples (male/female: 153/143) collected from the general population in seven Asian countries, China, India, Japan, Korea, Kuwait, Malaysia, and Vietnam, using high-performance liquid chromatography (HPLC) tandem mass spectrometry (MS/MS). On the basis of urinary BPA concentrations, we estimated the total daily intake. The results indicated that BPA was detected in 94.3 of the samples analyzed, at concentrations ranging from <0.1 to 30.1 ng/mL. The geometric mean concentration of BPA for the entire sample set from seven countries was 1.20 ng/mL. The highest concentration of BPA was found in samples from Kuwait (median: 3.05 ng/mL, 2.45 mu g/g creatinine), followed by Korea (2.17 ng/mL, 2.40 mu g/g), India (1.71 ng/mL, 2.09 mu g/g), Vietnam (1.18 ng/mL, 1.15 mu g/g), China (1.10 ng/mL, 1.38 mu g/g), Malaysia (1.06 ng/mL, 2.31 mu g/g), and Japan (0.95 ng/mL, 0.58 mu g/g). Among the five age groups studied (<= 19, 20-29, 30-39, 40-49, and >= 50 years), the highest median concentration of BPA was found in urine samples from the age group of <= 19 years. There was no significant difference in BPA concentrations between genders (male and female) or domicile of residence (rural and urban). The estimated median daily intakes of BPA for the populations in Kuwait, Korea, India, China, Vietnam, Malaysia, and Japan were 5.19, 3.69, 2.90, 2.13, 2.01, 1.80, and 1.61 mu g/day, respectively. The estimated daily intake of BPA in the seven Asian countries was significantly lower than the tolerable daily intake recommended by the U.S. Environmental Protection Agency. This is the first study to document the occurrence of and human exposure to BPA in several Asian countries.